Unexpected Triumph: A Case Report on Remarkable Survival After Paraquat Poisoning in a Young Male (KYAMC Journal, 2025)
Paraquat, a potent herbicide, is infamous for its high mortality rate following ingestion. This case report presents a rare instance of survival in a 17 years old male who intentionally ingested paraquat. The patient's atypical clinical course challenges the prevailing grim prognosis associated with paraquat poisoning, prompting a re-evaluation of management strategies. This report discusses potential factors contributing to the patient's survival, including early intervention, the use of high-dose corticosteroids, individual susceptibility, and the atypical presentation with less severe pulmonary involvement. The findings suggest that a nuanced understanding of paraquat toxicity is essential, acknowledging individual variabilities in response and exploring innovative therapeutic approaches. The unexpected positive outcome challenges existing paradigms in paraquat poisoning, urging further research to delineate the determinants of survival. Healthcare providers should consider this case when managing paraquat ingestions, emphasizing the potential for tailored interventions to improve patient outcomes.